The joint effect of aging and HIV infection on microstructure of white matter bundles. Issue 15 (4th July 2019) - Kuhn, Taylor; Jin, Yan; Huang, Chao; Kim, Yeun; Nir, Talia M.; Gullett, Joseph M.; Jones, Jacob D.; Sayegh, Phillip; Chung, Caroline; Dang, Bianca H.; Singer, Elyse J.; Shattuck, David W.; et al.
Abstract: Recent evidence suggests the aging process is accelerated by HIV. Degradation of white matter (WM) has been independently associated with HIV and healthy aging. Thus, WM may be vulnerable to joint effects of HIV and aging. Diffusion‐weighted imaging (DWI) was conducted with HIV‐seropositive ( n = 72) and HIV‐seronegative ( n = 34) adults. DWI data underwent tractography, which was parcellated into 18 WM tracts of interest (TOIs). Functional Analysis of Diffusion Tensor Tract Statistics (FADTTS) regression was conducted assessing the joint effect of advanced age and HIV on fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD), and radial diffusivity (RD) along TOI fibers. In addition to main effects of age and HIV on WM microstructure, the interactive effect of age and HIV was significantly related to lower FA and higher MD, AD, and RD across all TOIs. The location of findings was consistent with the clinical presentation of HIV‐associated neurocognitive disorders. While older age is related to poorer WM microstructure, its detrimental effect on WM is stronger among HIV+ relative to HIV− individuals. Loss of WM integrity in the context of advancing age may place HIV+ individuals at increased risk for brain and cognitive compromise.